Efficacy of sildenafil and high-dose anakinra in an MIS-C patient with pulmonary vasculitis: A case report - Francesco La Torre; Gerolmina Calabrese; Katia Signorile; Francesca Bizzoco; Carla Mastrorilli; Antonella Strippoli; Doriana Amato; Francesco Carella; Ugo Vairo; Paola Giordano; Leonardo Milella; Fabio Cardinale (Frontiers Media S.A., 2023)
Multisystem inflammatory syndrome in children (MIS-C) is a newly identified clinical entity still not very well known in terms of epidemiology, pathogenesis, and long-term outcome. Pulmonary involvement with acute respiratory failure is an unusual life-threatening complication of MIS-C, often a reason for admission to the pediatric intensive care unit (PICU) and the use of mechanical ventilation. We present a case of a 7-year-old male patient, previously healthy, hospitalized for MIS-C, treated with intravenous immunoglobulins (IVIG), high dose methylprednisolone, and anakinra. After 2 days of the aforementioned therapy, the patient presented with hypoxia (SatO2: 85% in ambient air room) and breathing difficulties. A chest computed tomography (CT) scan showed the presence of multiple bilateral basal parenchymal thickening and small basal pleural effusion and an arterial blood gas analysis revealed severe hypoxia (PaO2/FiO2 ratio, 170 mmHg). Because of a worsening of respiratory distress, the patient was transferred to the PICU, where invasive mechanical ventilation and a continuous infusion of anakinra (12 mg/kg/day) were started. An echocardiogram was performed, which showed an increase in pulmonary pressure (40 mmHg) with normal heart ejection fraction (55%), and the hypothesis of pulmonary vasculitis involving the pulmonary arterioles was made. Therefore, therapy with sildenafil (0.15 mg/kg/day) was promptly set up, with an immediate improvement of the clinical picture of respiratory failure, reduction of pulmonary pressure (23 mmHg), and subsequent extubation at 36 h with a regular clinical course until discharge. As far as we know, our case represents the first report of pulmonary vasculitis in an MIS-C patient. The use of sildenafil and high-dose continuous anakinra may represent a rescue therapy in cases of MIS-C with pulmonary vasculitis or with difficulty in extubation, allowing a short-term hospitalization in intensive care and improving the long-term outcome in these patients.